ANALISIS IMPLEMENTASI PARTICIPATORY PUBLIC DALAM MUSYAWARAH PERENCANAAN PEMBANGUNAN DAERAH DI KABUPATEN BLITAR - PEBRIA N, PORISA Febria (Jurnal Akuntansi AKUNESA, 2014)
This study aims to analyze the implementation participatory public in local development by using participatory governance as a model and focused on practical oriented. This study uses the approach of Good Government Governance with emphasis on the process by which the process of preparation, planning, policy formulation and involving all stakeholders.This study is adescriptive study with asurvey method. The main objective istoexplore, know, anddescribes the stateorthe phenomenonof public participationin development planning public in Blitar. Data collection techniques using semi-structured interviews and documentation. Analysis ofthe data in this study using interactive data analysis of Miles and Huberman which includes the step ofdata reduction, data presentation and conclusion. Determiningthe subject ofthisresearchis donebyusinga quotasample. Subdistrict studied includes District Wonodadi, District Udanawu, District and Sub-District Srengat Ponggok. The results showed that theimplementation ofthe participatory publicin Musrenbang is practical oriented.   Keywords: Good Government Governance, Musrenbang, ParticipatoryGovernance, participatory public